Multi-case review of the application of the precautionary principle in European Union Law and Case Law - Garnett, Kenisha; Parsons, David J. (Wiley, 2016)
The precautionary principle was formulated to provide a basis for political action to protect the environment from potentially severe or irreversible harm in circumstances of scientific uncertainty that prevent a full risk or cost-benefit analysis. It underpins environmental law in the European Union and has been extended to include public health and consumer safety. The aim of this study was to examine how the precautionary principle has been interpreted and subsequently applied in practice, whether these applications were consistent, and whether they followed the guidance from the Commission. A review of the literature was used to develop a framework for analysis, based on three attributes: severity of potential harm, standard of evidence (or degree of uncertainty), and nature of the regulatory action. This was used to examine 15 pieces of legislation or judicial decisions. The decision whether or not to apply the precautionary principle appears to be poorly defined, with ambiguities inherent in determining what level of uncertainty and significance of hazard justifies invoking it. The cases reviewed suggest that the Commission's guidance was not followed consistently in forming legislation, although judicial decisions tended to be more consistent and to follow the guidance by requiring plausible evidence of potential hazard in order to invoke precaution.
Keywords: Environment; European Union; health; legislation; precautionary principle